EVALUATION OF PERMANENT PRESERVE AREAS ON PLANIMETRIC SURFACE AND MODELED SURFACE IN ENVIRONMENTAL PROTECTION AREA OF PETRÓPOLIS MOUTAIN REGION - RJ - Fernando de Souza Antunes; Pedro Henrique Ferreira Coura; Manoel do Couto Fernandes (Geo UERJ, 2016)
doi: 10.12957/geouerj.2016.19220